Rationalisation of Central/Centrally Sponsored Schemes Implemented by the Ministry of Social Justice and Empowerment - Planning Commission (Planning Commission, 2001)
The Ministry of Welfare (renamed now as Ministry of Social Justice & Empowerment) was formed in September, 1985 to act as a nodal Ministry for disadvantaged and underprivileged sections like SCs, STs, OBCs, minorities, disabled, street children, aged etc. The Ministry has recently been bifurcated with a separate Ministry for Tribal Affairs.
Planning Commission
Planning Commission